Enterprise architecture implementation as interpersonal connection: Building support and commitment. (19th July 2019) - Dale, Mark; Scheepers, Helana
Abstract: Although architects are often made responsible for enterprise architecture implementation (EAI), they are dependent on business executives to fund the technology products and technology executives to provide staff and resources to support their implementation. Moreover, existing research into EAI focuses on the technical and social conditions associated with EAI success and failure and, to a lesser extent, on the influence of interpersonal interactions between architects and their stakeholders through which the EAI is enacted. Against that backdrop, we examine EAI from the perspective of the architects and their stakeholders with a focus on how architects can build commitment to and support for implementation of the selected technology products and programmes. Specifically, we rely on communities of practice (CoP) theory to investigate two cases of EAI with a focus on practices that enabled or prevented the architects from building communities with requisite commitment to and support for their efforts. We find that whilst the involved architects were required to liaise with business and technology stakeholders, their practices did not allow them to effectively build the necessary connections, and their EAI initiatives suffered accordingly. As a result, we theorize the permeability of community boundaries around architects as key to the success of EAI: When architects prioritize what they think is important over the views and concerns of business and technology stakeholders community, a dominant intra‐CoP perspective will emerge, and boundaries around the community of architects will be reinforced, preventing stakeholders with legitimate interests in the EAI to influence the process; in contrast, when architects prioritize engaging with the viewpoints and concerns of business and technology stakeholders community, boundaries will become permeable, and an intercommunity CoP will emerge, enabling knowledge sharing and negotiations between everyone with legitimate interests in the EAI.